Copy Number of an Integron-Encoded Antibiotic Resistance Locus Regulates a Virulence and Opacity Switch in Acinetobacter baumannii AB5075 - Sarah E. Anderson (American Society for Microbiology, 2020)
ABSTRACT We describe a novel genetic mechanism in which tandem amplification of a plasmid-borne integron regulates virulence, opacity variation, and global gene expression by altering levels of a putative small RNA (sRNA) in Acinetobacter baumannii AB5075. Copy number of this amplified locus correlated with the rate of switching between virulent opaque (VIR-O) and avirulent translucent (AV-T) cells. We found that prototypical VIR-O colonies, which exhibit high levels of switching and visible sectoring with AV-T cells by 24 h of growth, harbor two copies of this locus. However, a subset of opaque colonies that did not form AV-T sectors within 24 h were found to harbor only one copy. The colonies with decreased sectoring to AV-T were designated low-switching opaque (LSO) variants and were found to exhibit a 3-log decrease in switching relative to that of the VIR-O. Overexpression studies revealed that the element regulating switching was localized to the 5′ end of the aadB gene within the amplified locus. Northern blotting indicated that an sRNA of approximately 300 nucleotides (nt) is encoded in this region and is likely responsible for regulating switching to AV-T. Copy number of the ∼300-nt sRNA was also found to affect virulence, as the LSO variant exhibited decreased virulence during murine lung infections. Global transcriptional profiling revealed that >100 genes were differentially expressed between VIR-O and LSO variants, suggesting that the ∼300-nt sRNA may act as a global regulator. Several virulence genes exhibited decreased expression in LSO cells, potentially explaining their decreased virulence. IMPORTANCE Acinetobacter baumannii remains a leading cause of hospital-acquired infections. Widespread multidrug resistance in this species has prompted the WHO to name carbapenem-resistant A. baumannii as its top priority for research and development of new antibiotics. Many strains of A. baumannii undergo a high-frequency virulence switch, which is an attractive target for new therapeutics targeting this pathogen. This study reports a novel mechanism controlling the frequency of switching in strain AB5075. The rate of switching from the virulent opaque (VIR-O) to the avirulent translucent (AV-T) variant is positively influenced by the copy number of an antibiotic resistance locus encoded on a plasmid-borne composite integron. Our data suggest that this locus encodes a small RNA that regulates opacity switching. Low-switching opaque variants, which harbor a single copy of this locus, also exhibit decreased virulence. This study increases our understanding of this critical phenotypic switch, while also identifying potential targets for virulence-based A. baumannii treatments.